Profitabilitas, Ukuran Perusahaan, Growth, dan Corporate Social Responsibility Disclosure - Pratama, I Putu Dedy Wijaya; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2023)
The research aims to determine the effect of Profitability, Firm Size, and Growth on CSR Disclosure. The research was conducted on SRI-KEHATI indexed companies on the IDX in 2019-2021. The population of this study are all companies indexed by SRI-KEHATI and registered on the IDX during the 2019-2021 observation year. The sample in this study were all companies indexed in SRI-KEHATI and registered on the IDX during the observation year, namely 2019-2021, totaling 25 companies with 75 observations. Data analysis technique used multiple linear regression analysis. The results of the study show that profitability has a positive effect on CSR disclosure, which indicates that the higher the level of company profitability, the more Corporate Social Responsibility disclosure will increase. Company size has a positive effect on CSR Disclosure in large or small companies so that they have the same obligations and responsibilities for the environment around the company. Growth has a positive effect on CSR Disclosure which shows that the higher the company's growth rate, the more Corporate Social Responsibility Disclosure or CSR disclosure is made. Kata Kunci: Profitabilitas, Ukuran Perusahaan, Growth, CSR Disclosure